THE ROLE OF DECORATION IN SHAPING THE ENVIRONMENT - Самойлович, Валентин (SWorldJournal, 2025)
Essence of work is contained in that an equipment is examined not only as means of registration ofinterior on the last stage of development of design project, but as equivalent constituent of forming of environment of vital functions of man on the early s